CE: Managing Sepsis and Septic Shock. Issue 2 (February 2018) - Makic, Mary Beth Flynn; Bridges, Elizabeth
Abstract : N/A: Sepsis is a leading cause of critical illness and hospital mortality. Early recognition and intervention are essential for the survival of patients with this syndrome. In 2002, the Society of Critical Care Medicine (SCCM) and the European Society of Intensive Care Medicine (ESICM) launched the Surviving Sepsis Campaign (SSC) to reduce overall patient morbidity and mortality from sepsis and septic shock by driving practice initiatives based on current best evidence. The SSC guidelines have been updated every four years, with the most recent update completed in 2016. The new guidelines have increased the focus on early identification of infection, risks for sepsis and septic shock, rapid antibiotic administration, and aggressive fluid resuscitation to restore tissue perfusion. In 2014, the SCCM and the ESICM convened a task force of specialists to reexamine the definitions of terms used to identify patients along the sepsis continuum. In 2016, this task force published the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3). The new definitions and recommendations included tools, based on an updated understanding of the pathobiology of sepsis, that can be used to predict adverse outcomes in patients with infection. This article discusses the new SSC treatment guidelines, changes in the sepsis bundle interventions, and the Sepsis-3 definitions and tools, all of which enable nurses to improve patient outcomes through timely collaborative action. Abstract : This article discusses recent updates to the Surviving Sepsis Campaign's sepsis treatment guidelines, changes in the sepsis bundle interventions, and the new definitions and predictive tools introduced in the Third International Consensus Definitions for Sepsis and Septic Shock.